JURNAL AKUNTANSI MULTIPARADIGMA : Persepsi Konstituen Terhadap Akuntabilitas Keuangan Partai Politik (Studi di Kota Malang) - Masiyah Kholmi (Fak. Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The purpose of this research is to understand perceptions of constituents towards financial accountability of political parties and to support them in improving financial accountability. Independent variables in this research are political parties’ accountabilities. Samples in this research are constituents in Malang by Purposive Random Sampling. There are 102 respondents in this research. Data collection is carried out through distribution of questionnaires to respondents. Descriptive qualitative method was employed. The research has shown that according to constituents’ perceptions, financial accountability of political party is low, both in yearly financial report or fund campaign report. Next, there must be efforts to improve financial accountability, for example clear regulations from the government and the KPU, effective law enforcement, financial control of political party from independent teams; political party that is more transparent on campaign fund, and improvement of political party’s independence.